Answer:
=2xy^3x(xy-3)
Step-by-step explanation:
2x^2y4-6xy^3
=2xy^3x(xy-3)
=2xy^3x(xy-3)
Answer:
8 pounds of gummy bears.
Step-by-step explanation:
To find this answer I did:
40/30 = 4/3
Then,
4/3 x 6 = 24/3
This simplified is 8.
To check:
8/6 x 5 = 40/30
Answer:
u can find the answer in calculate
Using the discriminant of a quadratic equation, it is found that the quadratic equation would have one repeated solution for m = -3.
<h3>What is the quadratic equation?</h3>
The quadratic equation is given as follows:
mx² + 12x - 12.
<h3>What is the discriminant of a quadratic equation and how does it influence the solutions?</h3>
A quadratic equation is modeled by:
The discriminant is:
The solutions are as follows:
- If , it has 2 real solutions.
- If , it has 1 real solutions.
- If , it has 2 complex solutions.
For this problem, the coefficients are:
a = m, b = 12, c = -12.
Hence the discriminant is:
b² - 4ac = 144 + 48m.
We want it to be of 0, hence:
144 + 48m = 0
m = -144/48
m = -3.
More can be learned about the discriminant of a quadratic equation at brainly.com/question/19776811
#SPJ1
Yes your answer is solved correctly